Heavy metals and polycyclic aromatic hydrocarbons in sludge from three industrial wastewater treatment plants of the industrial parks of Isfahan province - Saeed Mardan; Asghar Ebrahimi; Mohammad Mehdi Amin; Seyed Alireza Momeni; Hamid Ghodousi; Mohammad Ali Adineh (International Journal of Environmental Health Engineering, 2015)
Aims: In this study, the characterization of heavy metals (HMs) and polycyclic aromatic hydrocarbons (PAHs) were investigated in three different industrial sewage sludges in industrial parks of Isfahan province, Isfahan, Iran. Materials and Methods: Sludge samples were collected from three dry bed wastewater treatment plants (WWTPs) within the province during of four seasons of 2011-2012. Gas chromatography-mass spectrometry and inductively coupled plasma were used to measure PAHs and HMs contents in sludge. Results: The average concentrations of Cd, Cr, Cu, Mo, Ni, Pb, As, Hg, and Se in sewage sludge were 305.67, 514, 1019, 6.46, 102.33, 1181.33, 277.33, 226.83, and 6.35 mg/kg dry weight (d.w.), respectively. The concentrations of HMs in most of the sludge samples were above the regulatory limits for the sludge class 1 and 2 to be used in agriculture in Iran. The levels of ∑8 PAHs varied from 92.33 μg/ the to 257.87 μg/kg d.w. in the sludge, that lower than the limitation value (6 mg/kg) recommended by the Europe Union and US Environmental Protection Agency for land application. Phenanthrene, pyrene, and fluorene were predominant isomers of PAH in sludge samples. The highest value was found in the Morchekhort WWTP. Conclusion: The concentration and composition of PAHs and HMs in sewage sludge varied and depended mainly on the quantity and type of industrial wastewater accepted by the WWTPs. There is a pyrene in sewage samples that is a carcinogenic. The concentration of HMs in sewage sludge was above of standard levels. Finally, we are not recommended the using of industrial sewage sludge in agriculture because of the high value of HMs was found in samples.